PRIORITY ALLOCATION METHOD OF THE BANDWIDTH DOWNLINK OF LTE TECHNOLOGY - Al-Zayadi, Haider; Al-Sharify, Mushtaq Talib; Khlaponin, Yuriy; AL-Sharify, Talib (Science-based technologies, 2015)
The results of developing a method of distribution of the frequency and time resources downlink technology LTE were presented. The proposed method is aimed to ensure the quality of service of wireless for users by allocating the user station required capacity in the downlink. A comparative analysis were done of the proposed method with known solutions of distribution time-frequency resources of LTE technology in terms of the overall performance of the downlink, the degree of balancing capacity, as well as the confidence level allocating user stations required capacity.